Association of Hypoactive and Hyperactive Delirium With Cognitive Function After Critical Illness. Issue 6 (June 2020) - Hayhurst, Christina J.; Marra, Annachiara; Han, Jin H.; Patel, Mayur B.; Brummel, Nathan E.; Thompson, Jennifer L.; Jackson, James C.; Chandrasekhar, Rameela; Ely, E. Wesley; Pandharipande, Pratik P.; Hughes, Christopher G.
Abstract : Objectives: Delirium, a heterogenous syndrome, is associated with worse long-term cognition after critical illness. We sought to determine if duration of motoric subtypes of delirium are associated with worse cognition. Design: Secondary analysis of prospective multicenter cohort study. Setting: Academic, community, and Veteran Affairs hospitals. Patients: Five-hundred eighty-two survivors of respiratory failure or shock. Interventions: We assessed delirium and level of consciousness using the Confusion Assessment Method-ICU and Richmond Agitation Sedation Scale daily during hospitalization. We defined a day with hypoactive delirium as a day with positive Confusion Assessment Method-ICU and corresponding Richmond Agitation Sedation Scale score less than or equal to 0 and a day with hyperactive delirium as a day with positive Confusion Assessment Method-ICU and corresponding Richmond Agitation Sedation Scale score greater than 0. At 3 and 12 months, we assessed global cognition with the Repeatable Battery for the Assessment of Neurologic Status and executive function with the Trail Making Test Part B. We used multivariable regression to examine the associations between days of hypoactive and hyperactive delirium with cognition outcomes. We allowed for interaction between days of hypoactive and hyperactive delirium and adjusted for baseline and in-hospital covariates. Measurements and Results: Hypoactive delirium was more common and persistent than hyperactive delirium (71% vs 17%; median 3 vs 1 d). Longer duration of hypoactive delirium was associated with worse global cognition at 3 (–5.13 [–8.75 to –1.51]; p = 0.03) but not 12 (–5.76 [–9.99 to –1.53]; p = 0.08) months and with worse executive functioning at 3 (–3.61 [–7.48 to 0.26]; p = 0.03) and 12 (–6.22 [–10.12 to –2.33]; p = 0.004) months; these associations were not modified by hyperactive delirium. Hyperactive delirium was not associated with global cognition or executive function in this cohort. Conclusions: Longer duration of hypoactive delirium was independently associated with worse long-term cognition. Assessing motoric subtypes of delirium in the ICU might aid in prognosis and intervention allocation. Future studies should consider delineating motoric subtypes of delirium. Abstract : Supplemental Digital Content is available in the text.